2017
DOI: 10.1111/desc.12555
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sports experience and executive function in 6–12‐year‐old children: independence from physical fitness and moderation by gender

Abstract: The purpose of this study was to evaluate the relationship between sports experience (i.e., tennis experience) and executive function in children while controlling for physical activity and physical fitness. Sixty-eight participants (6-12 years old, 34 males and 34 females) were enrolled in regular tennis lessons (mean = 2.4 years, range = 0.1-7.3 years) prior to the study. Executive functions, including inhibitory control (the Stroop Color-Word Test), working memory (the 2-back Task), and cognitive flexibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 55 publications
7
43
0
Order By: Relevance
“…Especially, frequency of tennis play was positively correlated with inhibitory control and working memory. Our findings are in accord with those of previous studies that demonstrated the positive relationship of sports participation to multiple aspects of executive functions in children (Crova et al, 2014;Ishihara et al, 2017a). Previous study had reported that tennis experience (just once a week) was not related to inhibitory control and working memory .…”
Section: Relationships Between Tennis Play and Executive Functionsupporting
confidence: 93%
See 2 more Smart Citations
“…Especially, frequency of tennis play was positively correlated with inhibitory control and working memory. Our findings are in accord with those of previous studies that demonstrated the positive relationship of sports participation to multiple aspects of executive functions in children (Crova et al, 2014;Ishihara et al, 2017a). Previous study had reported that tennis experience (just once a week) was not related to inhibitory control and working memory .…”
Section: Relationships Between Tennis Play and Executive Functionsupporting
confidence: 93%
“…The purpose of this cross-sectional study was to evaluate the association between the frequency of attending tennis lessons and the development of components of executive functions (i.e., inhibitory control, working memory, and cognitive flexibility) and their gender specificity. Given that dose-response relationships between exercise and cognition occur in children (Davis et al, 2011;Hillman et al, 2014), and a relationship that favors males has been reported (Booth et al, 2013;Drollette et al, 2016;Ishihara et al, 2017a), a higher TENNIS PLAY & COGNITION IN YOUTH 6 6 frequency of participation in tennis lessons is expected to be positively associated with improved executive functions, and the relationship is expected to be stronger in males than in females in the present study.…”
Section: Relationship Of Tennis Play To Executive Function In Childrementioning
confidence: 61%
See 1 more Smart Citation
“…This is particularly true for youth sport when the athletes are less specialized and, therefore, scouting only certain fundamentals (e.g., in volleyball, the attack percentage) would only provide a partial image of the athletes' abilities. Despite being relatively small, the research field that takes a developmental psychological approach to the study of sport performance in developing athletes [17][18][19][20] underlines the importance of understanding cognitive functioning and other individual differences in their development, in order to identify actual predictors of sport performance. Indeed, testing developing athletes can provide insights into the relation of individual differences and motor learning or sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…Developments in the brain functions and cognition of children in relation to physical activity are seen as cornerstones in their academic achievements [23]. It is noted that regular physical activity is thought to effect cognitive development through cerebral blood flow, improve nerve-hormone balance, regulate nutritional habits, and increase neural transmittance [24,25,43]. Under the light of these findings of literature, it can be said that an increase in the participation of children and adolescents in physical activities will positively affect their academic achievement.…”
Section: Conclusion and Discussionmentioning
confidence: 99%